VILLAGE FUND MANAGEMENT FOR COVID-19 HANDLING (Study in Kopek Village, Grobogan Regency, Central Java Province) - â€â€â€Ž â€â€â€Ž â€â€â€Ž â€â€â€Ž, SUPARWAN (DiE: Jurnal Ilmu Ekonomi dan Manajemen, 2022)
The purpose of this study was to analyze the practice of managing Village Funds in handling the COVID-19 pandemic based on applicable regulations. The research method used is descriptive qualitative with a case study approach. This research was conducted in Kopek Village, Godong District, Grobogan Regency. Data collection techniques by observation, interviews and documentation studies. The results of this study indicate that the management of village funds in handling COVID-19 is in accordance with applicable regulations. The procedure for allocating priorities for the use of Village Funds has been carried out in the Village planning and budgeting process. Changes in activities in handling COVID-19 were carried out through Village Deliberations which were followed by Changes in the Village Budget by refocusing activities and budgets to support the implementation of the Implementation of Restrictions on Micro-Based Community Activities and the Implementation of COVID-19 Handling Posts at the Village level as well as Direct Cash Assistance (BLT) and Cash Intensive Work (PKT). Keywords: Village Fund management, Handling COVID-19